Experimental Investigation on the Influence of Superplasticizer on Mechanical Behavior of Recycled Aggregate Concrete - Faruk Patowary; Mohammad Al Amin Siddique (Advances in Civil Engineering)
Needs for renovation and efficient use of available land space have led to the destruction of numerous deteriorated civil structures. Consequently, a huge amount of concrete demolished waste is generated annually worldwide. This demolished concrete waste has created an extra burden on the environment and landfills, making the development projects unsustainable. Demolished waste can be recycled and reused for sustainable development and to reduce the demand for fresh natural aggregates (NA). However, the poor performance of recycled aggregate concrete (RAC) compared to natural aggregate concrete (NAC) may be a significant drawback in the recycling and reusing of demolished concrete wastes. This limitation can be overcome by using a superplasticizer, which has the ability to improve different mechanical properties of concrete. The objective of this paper is to assess the effects of the superplasticizer on the mechanical characteristics of RAC. Concrete specimens were prepared to have replacement ratios (0%, 25%, 50%, and 100%) of fresh NA by recycled stone aggregates (RSA) and recycled brick aggregates (RBA). Half of the prepared concrete specimens were admixed with the superplasticizer, having 15% water reduction for concrete mixes. The obtained test results encourage the use of superplasticizers for improving the mechanical properties of RAC. It is observed that fresh, natural coarse aggregates in a concrete mix can be replaced with 50% RSA and 25% RBA with the addition of the superplasticizer without compromising the mechanical performance.